NMOS Performance of Low Boron Activation on Group V for Ultra-Shallow Junction Formation - Mohd Said, Muzalifah; Mohammed Napiah, Zul Atfyi Fauzan; Arith, Faiz; Mohd Noh, Zarina (Trans Tech Publications, 2013)
Fabrication of ultra shallow junctions with low contact resistances is desired to advance current CMOS technology. The low Boron activation on Group V for ultra shallow junction formation will makes the chip fabrication works effectively. Silvaco TCAD (Technology Computer Aided Design)manages simulation tasks and analyzing simulation results when ultra-shallow junction formation is using low-boron activation on Phosphorus, Antimony and Arsenic. A stimulate process like implantation, diffusion and dopant activation and epitaxial growth in different semiconductor materials has been analyzed as well as investigate the effects of energy of boron ion beams on ultra shallow junction formation. As a result, the electrical characteristics of NMOS structure by obtaining graph of ID – VGS and ID – VDS has been studied when there are variations in junction length (Xj), and gatelength (Lg).